Symmetry and Asymptotic Solutions for a Magnetohydrodynamics Darcy-Forchheimer Flow with a P-Laplacian Operator - Reyes-Garcia, E (American Institute of Physics, 2024)
Fluid flows under a p-Laplacian operator formulation have been considered recently in connection with the modeling of non-Newtonian fluid processes. To a certain extent, the main reason behind the interest in p-Laplacian operators is the possibility of determining experimental values for the constant p appearing in them. The goal of the present study is to introduce the analysis of solutions of a one-dimensional porous media flow arising in magnetohydrodynamics with generalized initial data under a Lebesgue integrability condition. We present a weak formulation of this problem, and we consider boundedness and uniqueness properties of solutions and also its asymptotic relation with the standard parabolic p-Laplacian equation. Then, we explore solutions arising from classical symmetries (including an explicit kink solution in the p = 3 case) along with asymptotic stationary and non-stationary solutions. The search for stationary solutions is based on a Hamiltonian approach. Finally, non-stationary solutions are obtained by using an exponential scaling resulting in a Hamilton-Jacobi type of equation. © 2024 Author(s).